2008
DOI: 10.1088/0960-1317/18/10/104012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the built-in stress level of AlN layers on the properties of piezoelectric vibration energy harvesters

Abstract: In this paper we investigated the effects of built-in stress on the dielectric and piezoelectric properties of sputtered AlN layers, meant to be implemented in micromachined piezoelectric vibration energy harvesters. Test structures including cantilevers, 4-point bending beams and metal-insulator-metal capacitors were manufactured with reactive sputtered AlN layers in a thickness range of 400-1200 nm. Various bias conditions during the deposition process allowed controlling the built-in stress level in the lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Figure 10a shows that the effective transverse coefficient has no dependency of the rf bias power. This is in good agreement with earlier published results from (Karakaya et al 2008). The mean transverse coefficients are between -1.0 and -1.2 C/m 2 .…”
Section: Piezoelectric Measurementssupporting
confidence: 93%
See 2 more Smart Citations
“…Figure 10a shows that the effective transverse coefficient has no dependency of the rf bias power. This is in good agreement with earlier published results from (Karakaya et al 2008). The mean transverse coefficients are between -1.0 and -1.2 C/m 2 .…”
Section: Piezoelectric Measurementssupporting
confidence: 93%
“…For the transverse piezoelectric coefficient the results are ambiguous. Ababneh et al (2010) reported an increase in the coefficient for thicker films, whereas Karakaya et al (2008) stated a decrease. Our investigations showed that the e 31,f coefficient has the tendency to increase for thicker films.…”
Section: Piezoelectric Measurementsmentioning
confidence: 97%
See 1 more Smart Citation
“…Most groups discussed compressive stress in AlN thin films. This can mainly be attributed to the incorporation of Ar in the film induced by a bias voltage V s , according to the explanations given in the literature [25,26]. This influence can be excluded in the present investigation due to the absence of any bias voltage, thus rendering a tensile stress of the film.…”
Section: Wafer Bow Measurementsmentioning
confidence: 52%
“…(10,11) Different piezoelectric materials have been developed in MEMS energy harvesters, such as PZT, (12) AlN, (13) ZnO, (14) PVDF, (15) and PMN-PT (16,17) single-crystal materials. Compared with other materials, the PMN-PT material exhibits outstanding piezoelectric properties that considerably surpass those of PZT ceramics by a factor of 4 to 5.…”
Section: Introductionmentioning
confidence: 99%